2015
DOI: 10.1021/acs.chemrestox.5b00038
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific, Intramolecular Cross-Linking of Pin1 Active Site Residues by the Lipid Electrophile 4-Oxo-2-nonenal

Abstract: Products of oxidative damage to lipids include 4-hydroxy-2-nonenal (HNE) and 4-oxo-2-nonenal (ONE), both of which are cytotoxic electrophiles. ONE reacts more rapidly with nucleophilic amino acid side chains, resulting in covalent protein adducts, including residue–residue cross-links. Previously, we demonstrated that peptidylprolyl cis/trans isomerase A1 (Pin1) was highly susceptible to adduction by HNE and that the catalytic cysteine (Cys113) was the preferential site of modification. Here, we show that ONE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
(78 reference statements)
0
15
0
Order By: Relevance
“…MS based approaches combined with enrichment procedures using biotin are increasingly being used to recognize site-specific modifications of proteins in complex proteomes from biological samples. Recently, Aluise et al [87] identified a peptidylprolyl cis/trans isomerase A1 (Pin1) adduct with HNE linked to the catalytic cysteine (Cys113) using click chemistry conjugation of biotin to Pin1 and LC–MS/MS analysis. In vitro covalent modification of the mitochondria protein NAD-dependent deacetylase sirtuin-3 (zrSIRT3) by HNE at Cys280 was recognized using biotin hydrazide (BH) treatment and avidin pull-down and further analysis by LC–MS/MS and MALDI-TOF/TOF [88] .…”
Section: Analysis Of Protein Lipoxidation Through Ms-based Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MS based approaches combined with enrichment procedures using biotin are increasingly being used to recognize site-specific modifications of proteins in complex proteomes from biological samples. Recently, Aluise et al [87] identified a peptidylprolyl cis/trans isomerase A1 (Pin1) adduct with HNE linked to the catalytic cysteine (Cys113) using click chemistry conjugation of biotin to Pin1 and LC–MS/MS analysis. In vitro covalent modification of the mitochondria protein NAD-dependent deacetylase sirtuin-3 (zrSIRT3) by HNE at Cys280 was recognized using biotin hydrazide (BH) treatment and avidin pull-down and further analysis by LC–MS/MS and MALDI-TOF/TOF [88] .…”
Section: Analysis Of Protein Lipoxidation Through Ms-based Methodsmentioning
confidence: 99%
“…Click chemistry has also been used to monitor the fate of HNE and oxidized phospholipids [87,97] and presents the advantage of the smaller tagging moiety, which is considered in most instances not to interfere with the metabolism or interactions of the labeled lipids. This type of labeling allows the derivatization of the tag by an alkyne-azide reaction ex vivo , that is, in tissue extracts, partially purified samples or permeabilized cells, thus facilitating detection, enrichment, imaging, etc .…”
Section: Detection Of Protein Lipoxidation Through Non-ms Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ONE facilitates the formation of more stable ␣-synuclein oligomers than those induced by HNE (17). More recently, Marnett and coworkers showed that ONE, rather than HNE, forms cross-links and alters the activities of pyruvate kinase M2 and peptidylprolyl cis/trans isomerase A1 in cells (18,19). Despite these interesting findings, the molecular interactions between ONE and complex proteomes and their dynamics remain uncertain with respect to the following issues.…”
mentioning
confidence: 99%
“…Thiols (in N -acetylcysteine and glutathione) very rapidly and imidazoles (in histidine and carnosine) less rapidly 15 add to the carbon−carbon double bond of ONE, but the resulting Michael adducts containing the 4-oxoalkanal moiety are even more reactive toward lysine than ONE. 16,17…”
mentioning
confidence: 99%